3y-3+y+19=8y+20-6y

Simple and best practice solution for 3y-3+y+19=8y+20-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-3+y+19=8y+20-6y equation:


Simplifying
3y + -3 + y + 19 = 8y + 20 + -6y

Reorder the terms:
-3 + 19 + 3y + y = 8y + 20 + -6y

Combine like terms: -3 + 19 = 16
16 + 3y + y = 8y + 20 + -6y

Combine like terms: 3y + y = 4y
16 + 4y = 8y + 20 + -6y

Reorder the terms:
16 + 4y = 20 + 8y + -6y

Combine like terms: 8y + -6y = 2y
16 + 4y = 20 + 2y

Solving
16 + 4y = 20 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
16 + 4y + -2y = 20 + 2y + -2y

Combine like terms: 4y + -2y = 2y
16 + 2y = 20 + 2y + -2y

Combine like terms: 2y + -2y = 0
16 + 2y = 20 + 0
16 + 2y = 20

Add '-16' to each side of the equation.
16 + -16 + 2y = 20 + -16

Combine like terms: 16 + -16 = 0
0 + 2y = 20 + -16
2y = 20 + -16

Combine like terms: 20 + -16 = 4
2y = 4

Divide each side by '2'.
y = 2

Simplifying
y = 2

See similar equations:

| 9+2z-5=9z+9-6z | | -5(1-5x)+5(8x-2)=11x-8x | | 4x^3-9x^2-9x=0 | | 7x+10+7x=24 | | -3x-20=2x+95 | | -6.8-3z-2.5-z=-3z+0.4 | | -2(t-3)-(t+6)=7 | | p=2l+2a | | -6=-5x+2x+9 | | 20-4(2w+1)=11w-4(11-w) | | 6-4n+3n=20-35 | | 6(x)=10 | | -4.6-5z-4.8-3z=-7-4.4 | | X^2-32x-64=0 | | 3b-6-12-5= | | 10-[2+(-9)3]= | | 7x+3-3x=27 | | 7t=80+9r | | 4(w+3)=w-16 | | 2x(x+1)=5-7x | | 6(8b+c-4a)-3(a-5c+8b)= | | 2(3+4x)=46 | | 9x+25=81 | | 3x-5+6x-2=5x+4x+7 | | 4x-5-3x=0 | | 9+25=81 | | .8w-.7w+.4w=3 | | x^2-10x+28=x^2+x+8 | | 2h+4=23-h | | Bx+Dy=L | | 4y+2x=-22 | | -(6x+2)-(8x-3)=8-(5x+1) |

Equations solver categories